YouTube as a Source of Patient Information for Prenatal Repair of Myelomeningocele - Castillo, Jayme; Wassef, Christina; Wassef, Audrey; Stormes, Katie; Berry, Anna E. (American Journal of Perinatology, 2019)
Objective With the increasing interest in fetal repair of myelomeningoceles (MMCs) over the last decade, it is reasonable to anticipate the need for high quality and accessible educational materials for patients. Patients often look to the internet for details regarding medical topics and specifically to YouTube for informative health-related videos. This study aims to analyze the content and shortcomings of currently available videos on YouTube regarding prenatal repair of MMCs.Study Design A YouTube search was performed on December 15, 2018, using the terms “fetoscopic surgery for neural tube defect” and “fetal surgery for neural tube defect.” The first 50 videos from each search were sorted by relevance and evaluated for video source (i.e., professional, personal, or other), target audience (medical professionals or general public), general descriptive statistics (i.e., video length, number of views, number of comments), and for five areas of content determined by the authors to constitute basic patient information regarding a surgical procedure: (1) procedure details, (2) eligibility criteria, (3) alternatives to surgery, (4) surgical risks, and (5) success rate. Accuracy of videos was not assessed.Results Of the 16 videos that met inclusion criteria, only 1 discussed fetoscopic surgery. The majority (62.5%) of videos were produced by a professional source and 81.3% were targeted toward the general public rather than medical professionals. Of the 16 videos, 10 (62.5%) included details regarding the surgery, 3 (18.8%) discussed eligibility criteria, and 8 (50.0%) mentioned alternatives to surgery. Additionally, seven videos (43.8%) discussed risks of the procedure and six (37.5%) included surgical success rate.Conclusion Only 2 of the 16 videos included all five areas of content that were evaluated, and both were in regard to open fetal repair. This study not only calls attention to the initial shortcomings of YouTube videos regarding fetal surgery for neural tube defects but also demonstrates the need for further investigation and more comprehensive analysis.
Keywords: myelomeningocele; fetal surgery; YouTube; patient education; fetoscopic surgery